Pengaruh Model Penyelesaian Problem Posing Terhadap Kemampuan Pemecahan Masalah Fisika Siswa Kelas XI SMK Negeri 1 Batang Angkola - erna, ernawati pasaribu; Sri Utami Khoilla Mora Siregar; Eni Sumanti Nasution (Universitas Gara Nusantara Padangsidimpuan, 2023)
This study aims to determine the effect of the problem posing learning model on students' physics problem-solving abilities. This study used a quasi-experimental method with a pretest-posttest control group design. This research was conducted at SMK Negeri 1 Batang Angkola with a total sample of 33 students. Sampling used a simple random sampling technique with data collection using a test of students' Physics Problem Solving Ability with an essay form of 10 questions. Students' physics problem-solving abilities use Polya's theory which includes understanding problems, making plans, doing calculations, and reviewing. Data analysis of the two groups used the t test. based on data processing shows that the value of Sig (2-tailed) <.001 <0.05, H0 is rejected. The physics problem solving ability of students who were taught using the problem posing learning model was higher with an average value of 85.53 than the physics problem solving abilities of students who were taught using the usual learning model carried out by teachers with a scientific approach to the 2013 curriculum with an average value of 52.5. this shows that there is an influence of problem posing learning models on students' physics problem-solving abilities in Impulse and Momentum material.